Preliminary results on tail energetics in the Moorish gecko, Tarentola mauritanica - Tommaso Cencetti; Piera Poli; Marcello Mele; Marco A.L. Zuffi (Acta Herpetologica, 2011)
The amount of lipids, proteins, ashes and water in original versus regenerated tails in Tarentola mauritanica shows differences, especially on the lipid fraction, supporting adaptive function hypotheses during reproduction of regenerated tails in geckos.